PENGARUH KOMUNIKASI ANTARPRIBADI DAN KECERDASAN EMOSIONAL TERHADAP KINERJA PADA KARYAWAN DI PT. ASURANSI RAYA - Wanda Griya Pudhag Wangi; Roni Faslah (Fakultas Ekonomi Universitas Negeri Jakarta, 2013)
Abstract The research aims to determine whether there is influence between Interpersonal Communication and Emotional Intelligence to Employee Performance in PT. Asuransi Raya. The method used is survey method with the path analysis. Test requirements analysis is used to find the regression equation obtained is Y = 0.417 Structure X1 + X2 + 0.324 0.614 0.614 Îµ2 and R2yx2x1 = X1 where X2 = 0.397 + 0.842 = 0.158 Îµ1 and R2x2x1. The results of both hypothesis test variables of interpersonal communication and emotional intelligence) simultaneously have an influence on employee performance, each independent variable is interpersonal communication and emotional intelligence has a significant influence on the dependent variable is the performance of employees. Key words: Interpersonal Communication, Emotional Intelligence, Employee, Performance.